Identificação de um modelo viscoelástico para o comportamento de relaxação de tensões do PTFE sob compressão e em temperatura ambiente - Macêdo, Salvino Cezar Mello de (2019)
The identification of viscoelastic models is important for the design of polymeric parts by making the mechanical behavior of the material predictable under critical conditions. However, the characterization of this behavior is costly and complex because it involves long duration tests. Therefore, the main objectives of this work are to characterize the mechanical behavior of PTFE, identify a viscoelastic model and subsequently apply this model in the simulation of the Shaft-Hole Coupling Test (SHCT), which simplifies the characterization of stress relaxation of polymers, to improve the test configuration. The characterization of the mechanical behavior of PTFE was performed via cyclic compressive tests with the application of progressive maximum stresses and recuperation plateaus. The identification of the viscoelastic model was achieved by employing stress relaxation tests along with computer simulations using finite element analysis (FEA) and an optimization workflow. These tests were performed using the digital image correlation (DIC) technique to measure the strain field in which the samples were submitted during the tests. The improvement of the SHCT was carried out by the FEA of the test with different geometry configurations using the software Abaqus, and the identification of the constitutive model parameters was achieved using the optimization software Isight. Under the tested conditions, the mechanical characterization identified the yield stress (between 5.0 and 5.5 MPa), the Poisson coefficient (0.46) and the elastic modulus (675 ± 25 MPa) of PTFE. The identified Parallel Rheological Framework (PRF) constitutive model was able the capture, with a good approximation, the stress relaxation behavior of PTFE and the SHCT simulations pointed out that the most suitable specimen geometry of the sample must resemble a tube with 4 mm thickness and 25 mm height.